PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PT SEGAR PRIMA JAYA - Kelvin, Kelvin; Saputra, Asron (SCIENTIA JOURNAL, 2019)
Nowadays, the world has entered the globalization era that has a large impact to the business world. This causes fierce competition among companies to seize market shares. Then companies must pay close attention to factors such as service quality and price so that they can contend in such fierce market competition. In order for a company to survive, a company must pay special attention to service quality. In a consumer’s purchase decision process, price is also a variable that does not lose in importance in the consumer’s purchase decision process. The study location of the research is at Komplek Ruko Windsor Square Block A Number 96, Batam. To find out whether service quality and price influences purchase decision at PT Segar Prima Jaya is the point of the research. Analysis of the data is helped with the software SPSS using multiple regression analysis. Results show that service quality and price have a significant positive effect either partially and simultaneously on purchase decision at PT Segar Prima Jaya.